Studies on Interaction Between Molybdenum(VI) and Human Serum Albumin By pH Displacement Method - Singh, R.P.; Kumar, Satyendra; Arora, S.K.; Kumar, R. (Asian Journal of Chemistry, 2010)
The interaction of Mo(VI) has been studied with human serum albumin using pH displacement method at two different temperatures and pH values. The apparent association constants and binding sites have been calculated with the help of Scatchard method. The binding data are suggested to be non-linear behaviour at pH 5.38 and 7.50 while linear behaviour at pH 9.85 and 11.50. The order of binding parameter and thermodynamic constants suggested that the interaction is pH and temperature dependents. The results are concluded that the guanidinium sites are major molybdenum ion binding sites.